2021
DOI: 10.1209/0295-5075/ac0c87
|View full text |Cite
|
Sign up to set email alerts
|

Present and future trends in spin ARPES

Abstract: Spin-orbit (SO) coupling combined with space inversion symmetry breaking is at the origin of the lifting of the spin degeneracy in the band structure of many materials. The momentum-dependent energy splitting and the degree of spin polarization are indicative of the strength and symmetry of the SO interaction, and enter in the figure of merit of essentially all conceptual designs aiming to control the electron spin degree of freedom in solids. Here we briefly review the role played by spin-and-angle-resolved p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Modern ARPES setups are often equipped with alkali metal (Na, K, R) sources that enable access to the unoccupied band structure by electron doping of the surface (see figure 2(d)) [56,59,60]. Furthermore, the possibilities of applying gate voltage (figure 2(e)) [57], strain (figure 2(f)) [8,58] or external magnetic field [61] while performing ARPES have recently been demonstrated.…”
Section: Sample Preparation and Measurement Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern ARPES setups are often equipped with alkali metal (Na, K, R) sources that enable access to the unoccupied band structure by electron doping of the surface (see figure 2(d)) [56,59,60]. Furthermore, the possibilities of applying gate voltage (figure 2(e)) [57], strain (figure 2(f)) [8,58] or external magnetic field [61] while performing ARPES have recently been demonstrated.…”
Section: Sample Preparation and Measurement Conditionsmentioning
confidence: 99%
“…In this review, we focus on arguably the most significant innovations in the field of photoemission from a rather technical perspective. More specialized reviews of ARPES studies of quantum materials can be found in [5][6][7][8][9]. The manuscript is organized as follows: First, we provide a brief introduction to the fundamental theory of the photoemission process, discuss experimental matters connected to photon energy, and reflect on sample requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the improvement of instrument technology, more types of ARPES have been invented, making it possible to analyze more degrees of freedom of electrons, such as spin, pseudospin, and valley states. Such as spin-resolved ARPES (Spin ARPES) can measure the electronic structures of spin up and down, providing important insights into spin correlation [75][76][77][78], NanoARPES can characterize the localized electronic structure of extremely small sample sizes due to the significant reduction in spot size [79,80], time-resolved APRES (TrARPES) has shown outstanding performance in detecting electron dynamics and electron time evolution due to the development of femtosecond lasers [81][82][83].…”
Section: Arpes Of Moiré Superlatticesmentioning
confidence: 99%
“…The level of sophistication that has been reached in measuring the spin-resolved electronic structure of materials [19], together with the recent report of a non-zero spin-momentum locking in centrosymmetric highly-overdoped cuprate superconductors [20], has opened a new frontier in this still poorly explored field. Here we use high resolution spin-and angle-resolved photoemission spectroscopy (spin-ARPES) to study the spin dependent electronic structure of cuprate superconductors as a function of momentum, doping, and family, spanning across both the electron-and hole-doped sides of the phase diagram.…”
mentioning
confidence: 99%